2022
DOI: 10.3390/mi13091406
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Random Forest for Solar Radiation Prediction Using Sunshine Hours

Abstract: Knowing exactly how much solar radiation reaches a particular area is helpful when planning solar energy installations. In recent years the use of renewable energies, especially those related to photovoltaic systems, has had an impressive up-tendency. Therefore, mechanisms that allow us to predict solar radiation are essential. This work aims to present results for predicting solar radiation using optimization with the Random Forest (RF) algorithm. Moreover, it compares the obtained results with other machine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The root mean square error (RMSE) value is a common way to determine how accurate a model is. There are also algorithms like decision trees, random forests, support vector regression, and neural networks that are not linear and can be used to solve regression problems [24][25][26][27].…”
Section: Regressionmentioning
confidence: 99%
“…The root mean square error (RMSE) value is a common way to determine how accurate a model is. There are also algorithms like decision trees, random forests, support vector regression, and neural networks that are not linear and can be used to solve regression problems [24][25][26][27].…”
Section: Regressionmentioning
confidence: 99%
“…They are less affected by noise in the data, robust to outliers, and stable. Villegas-Mier et al (2022) found that RFs gave a robust performance with similar results in two different scenarios. RFs delivered accurate and precise results when mapping SI at high latitudes (Babar et al, 2020).…”
Section: Related Literaturementioning
confidence: 68%
“…RF algorithms perform very well from the start without leveraging hyperparameters or custom data. It shows an accuracy of 89.30% 19 .…”
Section: Machine Learning Model For Pv Panel Cleaning Frequencymentioning
confidence: 94%